Implementation of Notary Responsibility for Loss of Assets Due to Notary Error - Cindy Zakiyyatul Miskiyya; Gunarto Gunarto; Umar Ma'ruf (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The objectives of this research are 1) To find out and explain the implementation of the notary's responsibility for the loss of a certificate due to a notary's mistake. 2) To find out and explain the obstacles and solutions to the implementation of the notary's responsibility for the loss of a certificate due to a notary's mistake. The method used by researchers is Juridical Empirical (sociolegal research)and the specification in this research is including analytical descriptive.The sources and types of data in this study are primary data. And secondary data obtained from literature studies relating to the theory of criminal liability and legal certainty. Based on the results of that researchThe implementation of the notary's responsibility for the loss of the minuta deed due to a notary's mistake, namely making an official report which then reports it to the Regional Supervisory Council or the Regional Supervisory Council which will be followed up with efforts to resolve it. Meanwhile, sanctions for a Notary whose minimum certificate is lost due to a notary's mistake may be subject to written warning sanctions, honorific temporary dismissal and dishonorable discharge. Of course, the imposition of this sanction will be carried out by the Regional Supervisory Council in accordance with the gravity or lightness of the violation committed by the notary concerned. The obstacle is making a report to the police with the contents of the report that the notary concerned has lost all important documents and files.